Profiling barriers to social inclusion in Ireland: the relative roles of individual characteristics and location - McGuinness, Seamus; Whelan, Adele; Bergin, Adele; Delaney, Judith (ESRI, 2018)
The study uses data from participants in the Department of Rural and Community Development’s Social Inclusion and Community Activation Programme (SICAP), administered by Pobal, to examine who is most likely to experience at least one of five barriers to social inclusion. The barriers are (a) belonging to a jobless household, (b) being a lone parent, (c) having a disability, (d) being homeless or affected by housing exclusion and (e) belonging to an ethnic minority.